Exploring intergenerational interactions with tiny social robots: a qualitative study - Hung, Lillian; Fu, Jiangning; Moros Villarroel, Veronica; Vega, Pristine; Zhao, Yong; Raval, Kruti; Santaella, Paulina; Shao, David (Frontiers in Dementia, 2025)
BackgroundWith the rapid aging of Canada’s population, more older adults are choosing to “aging in place,” yet they face challenges of social isolation and health risks. Emerging social robots are considered to have potential in reducing loneliness and promoting intergenerational communication.ObjectiveThis study aimed to explore how two tiny social robots (EMO and AIBI) support intergenerational interactions between older adults and university students, focusing on their emotional value, functionality, and perceived risks or limitations.MethodsWe applied the Interpretive Description qualitative methodology. Three focus groups were conducted in community settings, including 13 older adults (aged 51–81 years, including two in their early fifties who were active members of the lab’s older adult partner group) and 13 university students (>18 years). The study involved separate introductions to the robots for each group, intergenerational joint sessions, and thematic analysis, following COREQ guidelines.ResultsThree key themes emerged: (1) Emotional and companionship value—older adults highlighted improved mood, reduced loneliness, and practical benefits such as reminders; (2) Concerns about limitations and risks—students emphasized technical challenges, sustainability, and risks including over-reliance, communication barriers, and maintenance; (3) Bridging generations—both groups recognized the robots’ role in fostering shared engagement and emotional resonance across age groups.ConclusionTiny social robots show promise in enhancing older adults’ emotional well-being and fostering intergenerational connections. Differences in perspectives underscore the need for co-design approaches that integrate older adults lived experiences with younger people’ concerns for usability and safety.